Improve the Robustness of Range-Free Localization Methods on Wireless Sensor Networks using Recursive Position Estimation Algorithm - Prima Kristalina; Wirawan Wirawan; Gamantyo Hendrantoro (LPPM ITB, 2011)
The position of a sensor node at wireless sensor networks determines the received data sensing accuracy. By the knowledge of sensor positioning, the location of target sensed can be estimated. Localization techniques used to find out the position of sensor node by considering the distance of this sensor from the vicinity reference nodes. Centroid Algorithm is a robust, simple and low cost localization technique without dependence on hardware requirement. We propose Recursive Position Estimation Algorithm to obtain the more accurate node positioning on range-free localization technique. The simulation result shows that this algorithm has the ability on increasing position accuracy up to 50%. The trade off factor shows the smaller the number of reference nodes the higher the computational time required. The new method on the availability on sensor power controlled is proposed to optimize the estimated position.